PEMETAAN PERKEMBANGAN PENDIDIK DAN TENAGA KEPENDIDIKAN PENDIDIKAN NON FORMAL - Waspodo, Muktiono (JIV-Jurnal Ilmiah Visi, 2006)
This article is a review on the existence and the role of teachers and education personnel for nonformal education. The role of teachers and education personnel is under supervision of The Directorate General of Quality Improvement for Teachers and Education Personnel, through regulation No.8 2005, issued by Minister National Education. This article adopts the strategic planning of Directorate of Teachers and Education Personnel as the main reference. Critical reviews on the existence of teachers and education personnel for nonformal is very scarce. This is the mjhor cause of why many people tend to think â€œlearning is schoolingâ€. As a results, the term â€œschool teachers is more familiar to us than is nonformal education teachers. Though they function the same role as school teachers do. Even, they have to work harder . The article below discusses the development of functional education teachers, the organization and the strategic policies.